2003
DOI: 10.1016/s0002-9440(10)63625-5
|View full text |Cite
|
Sign up to set email alerts
|

RELP, a Novel Human Reg-Like Protein with Up-Regulated Expression in Inflammatory and Metaplastic Gastrointestinal Mucosa

Abstract: We screened expressed sequence tag databases for genes with up-regulated expression in inflammatory bowel diseases. A gene encoding a regenerating protein (REG)-like protein called RELP was identified and characterized. The relp gene encodes a major transcript of 1518 nucleotides, and two truncated splice variants. Unlike the reg genes, which form a cluster in chromosome 2, relp maps to chromosome 1p12-13.1. The predicted translation product is a 158-amino acid preprotein, showing 43% to 47% similarity to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
(19 reference statements)
5
48
0
Order By: Relevance
“…Total RNA (20 mg) was extracted 12 h after stimulation with cytokines or growth factors and analyzed by Northern blotting using 32 P-labeled cDNAs for REG IV and GAPDH mRNA. by Kämäräinen 17 and Oue et al, 18 and suggests functional roles for REG IV protein in normal colonic mucosa. However, in UC tissues REG IV expression is abundantly enhanced, and the distributions of positivity for REG IV and chromogranin A were apparently distinct.…”
Section: Effects Of Cytokines and Growth Factors On Reg IV Gene Exprementioning
confidence: 93%
“…Total RNA (20 mg) was extracted 12 h after stimulation with cytokines or growth factors and analyzed by Northern blotting using 32 P-labeled cDNAs for REG IV and GAPDH mRNA. by Kämäräinen 17 and Oue et al, 18 and suggests functional roles for REG IV protein in normal colonic mucosa. However, in UC tissues REG IV expression is abundantly enhanced, and the distributions of positivity for REG IV and chromogranin A were apparently distinct.…”
Section: Effects Of Cytokines and Growth Factors On Reg IV Gene Exprementioning
confidence: 93%
“…Cells were seeded on a 24-well plate at a density of 4x10 4 cells/well for HT-29 and 1.6x10 4 cells/ well for Caco-2/TC7. After 24 h, cells were stimulated with various concentrations (0.1-100 nM) of recombinant human REG4 (rREG4; BioVendor, Heidelberg, Germany) for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in numerous publications, increased expression of REG proteins in various tissues is often related to injury, inflammation or carcinogenesis supporting the multifunctionality of these proteins (1,2). REG4, the most recent member of the REG gene family to be characterized, was first identified as being up-regulated in ulcerative colitis which suggests that REG4 protein may play a role in inflammatory bowel diseases (3)(4)(5). It has been shown that REG4 is also overexpressed in cancers of the stomach, colon, pancreas and prostate (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 90%
“…1A). This gene encodes a secreted protein containing a conserved domain found in C-type lectin carbohydrate recognition domain (15). Another Reg family member, RegIIIγ, has convincingly been shown to serve an antibacterial function (16).…”
mentioning
confidence: 99%